Perfil epidemiol?gico e fatores associados ? infec??o por HIV/AIDS em adolescentes e adultos jovens - Pereira, Bianca de Souza (2013)
Introduction: There are approximately 34 million people have contracted HIV globally, it is estimated that 10 millions have between 15 and 24 years of age. The high incidence of HIV/AIDS in adolescents and young adults has been characterized a serious public health problem and has excelled in the International policies agendas for prevention and control. Objective: investigate the epidemiological profile and factors associated with HIV/AIDS in adolescents and young adults registered in the Reference Center STD/HIV/AIDS in Feira de Santana - BA, in the period from 2007 to 2011. Method: analytical study with lineation cross-sectional using data from SIS/CTA of Feira de Santana ? BA, totaling 1.032 adolescents and 2.736 young adults. The variables studied were: Socio-demographics (gender, age, city and area of residence, scholarity, occupation, marital status and skin color), concerning exposure with partner (condom use, reasons for non-use of condoms and partner type) and related to lifestyle (use of alcohol and other drugs, sharing syringes, presence and treatment of STDs, sexual orientation, multiple sexual partners and type of exposure to HIV). Were calculated simple and absolute frequencies and performed Stratified analysis of variables grouped, as well as calculated the prevalences (P) and the prevalence ratios (RP), to evaluate possible associations between the serological status and exposure factors in both sexes. Was adopted a confidence level of 95% and significance ? 0.05%. Results: adolescents and young adults showed equivalence regarding sociodemographic factors, however the seropositive women aged 20 to 24 years differed as for marital status, being that the majority were married. The occurrence of STDs in males was in greater proportion in the seropositives, with regard to females was observed the opposite, the majority had treated the STDs with help the health services, emphasizing that the proportions of those who were not treated or treated by themselves, was considerably higher in the seropositive group. Regarding condom use with steady or casual partner, over 80% reported do not make use, due to motivations linked to personal factors and related to the partner. As for the factors associated with HIV infection, in females, observed a significant association with the use of alcohol and other drugs, stable Union or marriage, beyond of the not utilization of condoms related to personal and external factors. In males, the significant results were linked to use of other drugs and to sexual orientation; in both sexes, associated with to stable partner be a carrier of HIV or STD. Conclusions: socio-demographic and behavioral characteristics can impact in the process of transmission and infection of disease, they become aspects of extremely relevance at the promotion of actions in service. In reaction to vulnerability of adolescent and young adult, it is considered fundamental the development of awareness and attitude change, in order to tackle the AIDS epidemic, seeking a type of comportment of self-preservation.